The role of RNA-interference in the pathogenesis of Fusarium graminearum on Hordeum vulgare and the evolutionary adaptation of Arabidopsis thaliana to Hyaloperonospora arabidopsidis derived small RNAs - Werner, Bernhard Timo; Justus Liebig University Giessen (My University, 2021)
The plant immune system evolved by the accumulation of counteracting innovations in pathogens and hosts and is often described as an ongoing “arms race”. Plants perceive microbe-associated molecular patterns (MAMPs) via cell surface pattern recognition receptors (PRRs) and pathogens interfere with this process of pattern-triggered immunity. This interference is mediated by effector proteins, leading to effector-triggered susceptibility. Plants evolved to perceive effectors or their activity via nucleotide-binding domain leucine-rich repeat receptors (NLRs), which leads to effector-triggered immunity. In 2013 a new class of non-protein pathogen effector molecules, exploiting the plant RNA interference (RNAi) machinery, was discovered. This process which is also utilized by hosts to defend against pathogens, is called cross-kingdom RNAi (ckRNAi). In this work ckRNAi is investigated in the important plant pathogen Fusarium graminearum (Fg) on the host plant barley. As a first step barley plants were treated with long double-stranded RNAs (dsRNAs) to silence the fungal Argonaute (AGO) and Dicer-like (DCL) genes (Chapter I). This silencing was effective and reduce disease symptoms in barley, showing that FgAGOs and FgDCLs are important for pathogenesis. With the role of FgDCLs and FgAGOs shown, FgDCL knock-out (KO) mutants were further investigated to show the involvement of ckRNAi in the pathogenesis of Fg (Chapter II). Due to the necessity of DCLs in the production of sRNAs, fungal ckRNAi should be prevented. Barley Fg-sRNA target genes were highly expressed during the interaction with KO-mutants, disease symptoms were reduced and degradation products of Fg-sRNA targets present in plants infected with the wild type fungus lacked in plants infected with DCL-KO mutants. Together, this shows the involvement of ckRNAi in the pathogenesis of Fg. Yet, the biological significance of ckRNAi remained debatable, due to the roles of DCL genes in the internal gene regulation of Fg. To address this, a new bioinformatics workflow was developed to calculate the likelihood of observing the actual complementarity of sRNA-mRNA interactions, under conservation of amino acid (AA) sequence and following the organisms’ codon frequency (Chapter III). Intriguingly, Fg-sRNAs showed an unlikely high complementarity between pathogen sRNAs and host mRNAs, while following the effector hypothesis one would expect hosts to prevent ckRNAi. To resolve this apparent contradiction, the hypothesis was formed, that plants utilize ckRNAi to perceive pathogen sRNAs and react accordingly. This resembles the way NLRs and PRRs perceive protein effectors and MAMPs, respectively, leading to Immunity, and would be a yet undescribed and new step in the arms race between pathogen and plant, bearing enormous potential for future applications in the generation of disease resistant crops.
Keywords: Phytopathology; RNA interference; Fusarium graminearum; Hordeum vulgare; Arabidopsis thaliana; Hyaloperonospora arabidopsidis; cross-kingdom RNA interference; ddc:570; ddc:580; ddc:630